MENCEGAH FRAUD DI DALAM INDUSTRI PERBANKAN - Ali Akbar, Mhd. (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
This study aims to determine the effect of Internal Audit, Ethical Behavior and Whistleblowing System on Fraud Prevention. The population of this research is the frontliner and the Head of the Frontliner who works at PT Bank Central Asia Tbk. KCU Alam Sutera. This research method uses qualitative methods by distributing research questionnaires involving 50 respondents. In this study the authors used SPSS 25 in processing data. From the results of the partial hypothesis test it was found that the internal audit variable had no effect on fraud prevention variables. On the other hand the ethical behavior variable and the whistleblowing system variable influence the fraud prevention variable. And the results of the simultaneous hypothesis test show that all independent variables influence the dependent variable together